2018
DOI: 10.1016/j.ajhg.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Human-Specific Tandem Repeat Associated with Bipolar Disorder and Schizophrenia

Abstract: Bipolar disorder (BD) and schizophrenia (SCZ) are highly heritable diseases that affect more than 3% of individuals worldwide. Genome-wide association studies have strongly and repeatedly linked risk for both of these neuropsychiatric diseases to a 100 kb interval in the third intron of the human calcium channel gene CACNA1C. However, the causative mutation is not yet known. We have identified a human-specific tandem repeat in this region that is composed of 30 bp units, often repeated hundreds of times. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 78 publications
1
99
0
Order By: Relevance
“…The ability to detect motifs that have differential usage between populations brings the possibility of detecting differential motif usage between cases and controls in association studies. This can help distinguish stabilizing versus fragile motifs (Braida et al 2010) , or resolve some of the problem of missing heritability by discovering new associations between motif and disease (Song, Lowe, and Kingsley 2018) . Each locus is converted to a de Bruijn graph, from which the collection of graphs is the RPGG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to detect motifs that have differential usage between populations brings the possibility of detecting differential motif usage between cases and controls in association studies. This can help distinguish stabilizing versus fragile motifs (Braida et al 2010) , or resolve some of the problem of missing heritability by discovering new associations between motif and disease (Song, Lowe, and Kingsley 2018) . Each locus is converted to a de Bruijn graph, from which the collection of graphs is the RPGG.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 70% of insertions and deletions discovered by LRS assemblies greater than 50 bases are in STR and VNTR loci (Chaisson et al 2019) , accounting for up to 4 Mbp per genome. Furthermore, LRS assemblies reveal how VNTR sequences differ kilobases in length and by motif composition (Song, Lowe, and Kingsley 2018) . Here we propose using a limited number of human LRS genomes sequenced for population references and diversity panels (Chaisson et al 2019;Audano et al 2019;Seo et al 2016;Shi et al 2016) to improve how VNTR variation is detected using SRS.…”
Section: Introductionmentioning
confidence: 99%
“…Cacna1c heterozygous knockout mice showed phenotypes that suggest a decrease in dopamine, such as a decrease in exploratory behavior and a decrease in response to amphetamine . However, a recent study showed that the risk allele of CACNA1C associated with BD is associated with the number of human‐specific 30‐base tandem repeats, and this repeat sequence acts as an enhancer that potentially changes the expression of CACNA1C or neighboring genes . Thus, simple knockout mice may not reveal the mechanism of this genetic association.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The best example of this is the GWAS locus located in the third intron of CACNA1C, which is one of the strongest and best-replicated associations for schizophrenia (SCZ) and bipolar disorder (BD) 46 . Past studies on this locus in neurons or brain tissues suggested a transcription regulatory role, but the causative variants are still unknown [47][48][49][50] . Unexpectedly, we found a strong hiPSC-specific CTCF loop connecting the GWAS locus to the CACNA1C promoter; this loop weakens when the gene is upregulated during neurogenesis and in brain tissues, possibly due to transcription elongation 51 (Fig.…”
Section: Chromatin Loop Outperforms Eqtl In Identifying Gwas Target Gmentioning
confidence: 99%